2021
DOI: 10.1016/j.xjidi.2021.100042
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review of Real-World Effectiveness and Safety of Dupilumab for Atopic Dermatitis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 147 publications
(266 reference statements)
2
56
1
Order By: Relevance
“…2 Conjunctivitis was observed in 8.6%-22.1% of patients during dupilumab therapy in AD clinical trials, whereas it was even more prevalent, up to 62%, in real-world reports. 1 However, in most cases, conjunctivitis was mild-to-moderate and transient. 2,3 In fact, only 2 of 2629 patients discontinued dupilumab because of ocular adverse events.…”
Section: One Of the Adverse Effects Of Dupilumab Is Conjunctivitis Withmentioning
confidence: 98%
See 1 more Smart Citation
“…2 Conjunctivitis was observed in 8.6%-22.1% of patients during dupilumab therapy in AD clinical trials, whereas it was even more prevalent, up to 62%, in real-world reports. 1 However, in most cases, conjunctivitis was mild-to-moderate and transient. 2,3 In fact, only 2 of 2629 patients discontinued dupilumab because of ocular adverse events.…”
Section: One Of the Adverse Effects Of Dupilumab Is Conjunctivitis Withmentioning
confidence: 98%
“…Dupilumab is an antibody against the interleukin (IL)-4R alpha subunit and blocks the signaling of IL-4 and IL-13. 1 It is approved for AD, bronchial asthma, and chronic sinusitis with nasal polyps in Japan.…”
mentioning
confidence: 99%
“…There are phase 3 studies and real-world data that have shown dupilumab is effective in most patients with AD, with a relatively safe profile. In a review of real-world data, 1 the percentage of patients with AD who achieved EASI75 (ie, an improvement in eczema severity by 75% based on Eczema Area and Severity Index) is approximately 70% over a period of 40 weeks. This is consistent with the 65% efficacy rate in the 52-week Liberty AD Chronos phase 3 trial, in which topical corticosteroids (TCS) were allowed.…”
mentioning
confidence: 99%
“…2 However, although most patients have a satisfactory response to dupilumab, it is believed that a considerable number of patients have failed to respond to dupilumab in the real world. 1 The questions are, what percentage of AD patients have an inadequate response to dupilumab, and is there a way to predict them?…”
mentioning
confidence: 99%
See 1 more Smart Citation